Improving the Efficiency of the MPU-6050 Sensor Module for Inertial Drone Navigation - Alizada, Tahir; Sabziev, Elkhan; Heydarov, Namig (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
We investigate the problems of noise reduction in navigation data supplied by an accelerometer and a gyroscope. The MPU-6050 sensor module, which is often a component of drone navigation systems, was used in the experiments. To smooth the data, the use of "simple averaging method" and "moving average method" is recommended. We show experimentally that the data smoothing methods reduce the errors by more than 10 times. It is also shown that the "simple averaging method" can reduce the hardware load by more than 10 times compared to other data processing methods.